2020
DOI: 10.1590/1806-9282.66.10.1437
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of left atrial thrombus in acute ischemic stroke patients without atrial fibrillation: A single-center cross-sectional study

Abstract: SUMMARY INTRODUCTION: The present study aimed to determine independent predictors of left atrial thrombus (LAT) in acute ischemic stroke (AIS) patients without atrial fibrillation (AF) using transesophageal echocardiography (TEE). METHODS: In this single-center, retrospective study, we enrolled 149 consecutive AIS patients. All of the patients underwent a TEE examination to detect LAT within 10 days following admission. Multivariate logistic regression analysis was performed to assess independent predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The prevalence of LAA thrombus in this study was 6.2% (9 of 144 patients). 6 A higher rate (9.3%, 14 of 149 patients) of LAA thrombus was noted in the retrospective study by Cinar et al 5 Our study identified LAA thrombus in 15 of 223 patients (6.7%). These results suggest that it is reasonable to consider the presence of LAA thrombus in cases of newonset ischaemic stroke who exhibit normal sinus rhythm on 12-lead ECG.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…The prevalence of LAA thrombus in this study was 6.2% (9 of 144 patients). 6 A higher rate (9.3%, 14 of 149 patients) of LAA thrombus was noted in the retrospective study by Cinar et al 5 Our study identified LAA thrombus in 15 of 223 patients (6.7%). These results suggest that it is reasonable to consider the presence of LAA thrombus in cases of newonset ischaemic stroke who exhibit normal sinus rhythm on 12-lead ECG.…”
Section: Discussionmentioning
confidence: 46%
“…38 39 Limited information is available regarding the predictors of LAA thrombus in patients who had a stroke with baseline sinus rhythm. 5 6 In such patients, while a recent study showed that mean platelet volume, renal function, LVEF and LAA flow velocity were independent predictors of LAA thrombus, 5 another study revealed that LA peak strain and high-sensitivity C reactive protein were associated with LAA thrombus, but not mean platelet volume, renal function or LVEF. 6 In the current study, the adjusted model revealed that patients with SEC had a significantly higher probability of LAA thrombus formation.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…https://doi.org/10.1590/ 1806-9282.20210463 We are happy to read the article 1 published by Cinar research team. Their findings suggest that patients with acute ischemic stroke with low ventricular ejection fraction and elevated platelet volume should undergo further transespiratory echocardiogram to verify the possibility of myocardial origin.…”
Section: Commentarymentioning
confidence: 99%